Очерки русской культуры XVIII века: [в 4 частях (главный редактор Б. А. Рыбаков]) - Рыбаков Борис Александрович (1990)
Экземпляры: КХ (20100427) / Инвентарный номер: 972119 / Цена: / Сис.шифр: 63.3(2)4 / Авт.знак: О-95 / ГРНТИ: 03 / ББК: 63.3(2)51